Identification of the core genes in Randall’s plaque of kidney stone and immune infiltration with WGCNA network - Yu, Lingyun; Li, Gefei; Jin, Shiyao; Su, Jiahong; Li, Shoulin (Frontiers in Genetics, 2023)
Background: Randall’s Plaque is regarded as the precursor lesion of lithiasis. While traditional bioinformatic analysis is limited and ignores the relationship with immune response. To investigate the underlying calculi formation mechanism, we introduced innovative algorithms to expand our understanding of kidney stone disease. Methods: We downloaded GSE73680 series matrix from the Gene Expression Omnibus (GEO) related to CaOx formation and excluded one-patient GSE116860. In RStudio (R version 4.1.1) platform, the differentially expressed genes (DEGs) were identified with limma package for GO/KEGG/GSEA analysis in clusterProfiler package. Furthermore, high-correlated gene co-expression modules were confirmed by WGCNA package to establish Protein-Protein interaction (PPI) network. Finally, the CaOx samples were processed by the CIBERSORT algorithm to anchor key immune cells group and verified in validation Series Matrix GSE117518. Results: 840 up-regulated and 1065 down-regulated genes are identified in this study. The GO/KEGG results revealed fiber-related or adhesion-related terms and several pathways besides various diseases from DO analysis. Moreover, WGCNA selected highly correlated modules to construct Protein-Protein interaction (PPI) network. Finally, Sixteen immune cells are supposed to participate in urolithiasis pathology and are related to hub genes in PPI network, which are proven significant in validation Series Matrix GSE117518. Conclusions: Randall’s Plaque may relate with genes (DCN, LUM, P4HA2) and immune cells(M2 Macrophages, resting Mast cells), these findings could serve as potential biomarkers and provide new research directions in further research.